2015
DOI: 10.1093/nar/gkv260
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of yeast DNA polymerase δ-mediated strand displacement synthesis by 5′-flaps

Abstract: The strand displacement activity of DNA polymerase δ is strongly stimulated by its interaction with proliferating cell nuclear antigen (PCNA). However, inactivation of the 3′–5′ exonuclease activity is sufficient to allow the polymerase to carry out strand displacement even in the absence of PCNA. We have examined in vitro the basic biochemical properties that allow Pol δ-exo− to carry out strand displacement synthesis and discovered that it is regulated by the 5′-flaps in the DNA strand to be displaced. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
(79 reference statements)
0
27
0
Order By: Relevance
“…It was previously shown that high concentrations of salt inhibit strand displacement synthesis by Pol δ exo − ( 28 ). To ask whether the salt concentration also influences strand displacement synthesis by Pol ε, we performed assays in the presence of various concentrations of NaAc (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that high concentrations of salt inhibit strand displacement synthesis by Pol δ exo − ( 28 ). To ask whether the salt concentration also influences strand displacement synthesis by Pol ε, we performed assays in the presence of various concentrations of NaAc (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We designed substrates containing flaps with a length of 1, 5, 10 or 20 nucleotides. It was recently shown that strand displacement synthesis by Pol δ exo − (pol3-5DV) is strongly inhibited when the blocking primer contains longer flaps ( 28 ). In contrast to Pol δ exo − , our results show that Pol ε exo − is not hindered by the flaps and is able to synthesize DNA to the end of the template by displacing the entire blocking oligo irrespective of the flap size (Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…DNA polymerase δ wild-type and D520V (Pol δ DV ), purified as previously described ( 27 29 ). Replication Protein A (RPA), PCNA and Replication Factor C (RFC) were purified from E. coli overproduction strains as described ( 19 , 30 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, rad27 rnh35 mutant cells do not support viability, suggesting that Fen1 and RNAase H2 have redundant roles in Okazaki fragment processing 6 . The Polδ- dependent strand displacement of the previous Okazaki fragment, which is stimulated by proliferating cell nuclear antigen (PCNA), is counterbalanced by its 3’–5’nucleolitic proof reading activity that resects the growing 3’ end of the Okazaki fragment 2 , 4 , 7 . Mutations in the proof reading activity of DNA polymerase δ are lethal in combination with RAD27 deletion, suggesting that DNA polymerase δ-dependent degradation of the growing 3’ ends of the Okazaki fragments and Fen1 synergize in the maturation of the Okazaki fragments 8 .…”
Section: Introductionmentioning
confidence: 99%